EVALUASI PENGGUNAAN MEDIA SOSIAL INSTAGRAM UNTUK PEMASARAN ONLINE PRODUK OLAHAN SALAK UNIT KELOMPOK WANITA TANI (KWT) PURWOBINANGUN - Dian Rizki Tri Wahyu Nanda; Anjar Ruspita Sari; Pujo Saroyo (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Purwobinangun Farmer Women's Group (KWT) is an association that accommodates the activities of women farmers in Purwobinangun, Pakem District, Sleman Regency, Yogyakarta Special Region. The Covid-19 pandemic caused KWT Purwobinangun's harder efforts to sell processed snake fruit products due to large-scale social restrictions (PSBB). The selling difficulties of their product in this situation have resulted in a decrease in income so that members of the association need to innovate their marketing activity to reach consumers easily. The objective of this study was to evaluate the online marketing of processed snake fruit by KWT Purwobinangun using Instagram. The application of Instagram in processed snake fruit marketing began with information gathering, observations, questionnaires distribution, e-mail accounts creation, Instagram accounts creation, as well as online marketing activities. The result showed that Instagram account @pasar_springmerapi as online marketing for KWT Purwobinangun took 4 months to be recognized by the public. KWT Purwobinangun member stated that online marketing using the @pasar_springmerapi (Instagram account) resulted in consumer convenience of various product types finding and product descriptions offered so that the marketing distribution is more effective. However, the activities of product ordering were considered inefficient due to KWT Purwobinangun did not have a centralized admin to organize various products order. Thus, to improve the marketing effort of processed snake fruit, it is necessary to do information updates continuously.